A facile one-step hydrothermal synthesis of HfO2/graphene nanocomposite and its physio-chemical properties - Sagadevan, Suresh; Chowdhury, Zaira Zaman; Johan, Mohd Rafie; Rafique, Rahman Faizur (IOP Publishing, 2018)
A facile one-step hydrothermal synthesis of Hafnium oxide/Graphene (HfO 2 /Gr) Nanocomposite was successfully synthesized. The crystallinity index and the overall phase transformation process during the synthesis process was observed using x-ray diffraction (XRD) pattern. The surface morphology of the prepared composite was analyzed using Scanning electron microscopy (SEM). Transmission electron microscopy studies (HR-TEM) were conducted to measure the particle sizes. The presence of different types of functional groups was confirmed using FT Raman spectroscopy. UV-Visible spectrum analysis with optical ingestion was conducted to observe the optical properties of the prepared sample. The dielectric properties and conductivity of the prepared sample were investigated whereby the frequencies and the temperatures were altered. The results showed that both the phenomenon of the dielectric consistent and the dielectric loss were frequency and temperature dependent. The thermal conductivity behavior of the prepared samples was checked by calculating AC conductivity values at various temperatures.